(untitled) (Tikrit Journal For Political Science, 2025)
The study focuses on international cooperation in Libya and its impact on Arab security. The study attempts to clarify the real goal of the international military intervention in Libya in 2011, and to monitor the mechanisms followed in the process of communication and coordination between all foreign forces present in Libya and the impact of this on Arab security. The study concluded that the United States and its allies deliberately turned Libya into an arena for confrontation and internal fighting carried out by proxy for international and regional forces, for multiple purposes and goals, the most prominent of which is to occupy the international and regional parties present in this crisis, in addition to trying to drag the various powers to be the main parties in the crisis, especially those opposing it, in order to try to drain them militarily and economically. Also, increasing the parties to the crisis leads to prolonging its duration due to the difficulty of finding consensual solutions between the various parties.